2024
DOI: 10.3389/fendo.2024.1340664
|View full text |Cite
|
Sign up to set email alerts
|

Phthalate metabolites and sex steroid hormones in relation to obesity in US adults: NHANES 2013-2016

Jiechang Zhang,
Wen Gu,
Shilei Zhai
et al.

Abstract: BackgroundObesity and metabolic syndrome pose significant health challenges in the United States (US), with connections to disruptions in sex hormone regulation. The increasing prevalence of obesity and metabolic syndrome might be associated with exposure to phthalates (PAEs). Further exploration of the impact of PAEs on obesity is crucial, particularly from a sex hormone perspective.MethodsA total of 7780 adult participants in the National Health and Nutrition Examination Survey (NHANES) from 2013 to 2016 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 61 publications
0
0
0
Order By: Relevance
“…Obesity and MetS represent significant health challenges in the U.S, and they are associated with disturbances in sex hormone regulation [ 8 ]. Human sex hormone-binding globulin (SHBG) is a serum protein with a strong and specific ability to bind to androgens and estrogens [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity and MetS represent significant health challenges in the U.S, and they are associated with disturbances in sex hormone regulation [ 8 ]. Human sex hormone-binding globulin (SHBG) is a serum protein with a strong and specific ability to bind to androgens and estrogens [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research has revealed that the prevalence of low SHBG levels in the American population is 3.3% in males and 2.7% in females. Risk factors associated with low SHBG levels include elevated body mass index, diabetes, race (Hispanic, non-Hispanic black, or non-Hispanic white), chronic obstructive pulmonary disease, coronary heart disease, smoking and exposure to phthalates [ 8 , 10 ]. SHBG levels are independently associated with the risk of diabetes, dementia, non-alcoholic fatty liver disease, hypertension, coronary heart disease, and ischemic stroke [ 11 14 ], all of which are associated with a higher risk of MetS.…”
Section: Introductionmentioning
confidence: 99%